Business Feasibility Analysis on Shark Fin Production at UD. - Alvian, Fahri; Moh. Jufriyanto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2025)
This study was performed at UD. Rovita in Gresik City. UD. Rovita is a food manufacturing enterprise that makes shark fin chips and has never performed a business feasibility assessment throughout its operations. This research is to evaluate the viability of the shark fin chip enterprise at UD. Rovita. This research employs a cost-profit analysis methodology for data evaluation. To assess business feasibility, the formulas used are revenue cost (R/C), benefit cost ratio (B/C), and return on investment (ROI). The study's findings indicated that annual sales of shark fin chips amounted to Rp. 1,000,000,000, while manufacturing expenditures were Rp. 537,949,483 per year. The production expenses include fixed expenditures amounting to Rp. 519,600,000 and variable costs of Rp. 18,349,483 per year. The data analysis revealed a monthly profit of Rp. 462,050,517. The business feasibility calculation, represented by the R/C ratio, which compares income to total expenses, yields a result of 1.86, indicating that 1.86>1. The B/C ratio is the assessment of profit relative to total production expenses, which exceeds zero, with a comparative value of 0.86 or 0.86>0. The ROI value, derived from the comparison of profit and production capital, is 86%. It may be inferred that the firm is both lucrative and viable to operate.